Lontar Kuttara Kanda Dewa Purana Bangsul (Kajian Pendidikan Lingkungan) - Putu Diantika; Ni Nyoman Dian Tri Utami (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Environmental problems have occurred in almost all corners of the world, this happens because in everyday life humans act without using ethics and morals towards the environment. The planting and development of environmental moral values is carried out through environmental education oriented to local wisdom. Lontar as a result of traditional literary works is one of the local wisdoms of the Balinese people and even the archipelago. The lontar which represents the noble values of nature and the environment that are respected by the Balinese people, one of which is the Kuttara Kanda Dewa Purana Bangsul lontar. The story of the Kuttara Kanda Dewa Purana Bangsul ejection contains dominant symbols related to ecology which then results in a study of environmental problems, and the Kuttara Kanda Dewa Purana Bangsul ejection story raises the socio-ecological life of the Balinese people through the disclosure of educational values in it so that it can be used as a reference in implementation of environmental-based education programs to address sustainable environmental crises. In the lontar Kuttara Kanda Dewa Purana Bangsul, it is narrated that Hyang Pasupati as the main character can be observed from the intensity of involvement in the story, the story in this script is set in the natural environment of Bali. The mandate contained in the lontar story of Kuttara Kanda Dewa Purana Bangsul is the attitude of devotion to the gods. The function of the Kuttara Kanda Dewa Purana Bangsul text can be concluded that the placement of the gods in the natural environment of Bali has an impact on the establishment of good relations between humans and God which is divided into religious and ethical functions. The value of environmental education in the story of Kuttara Kanda Dewa Purana Bangsul is in the form of efforts to conserve the physical environment through the Sad Krti concept including: girikrti, wanakrti, sagarakrti, ranukrti, swikrti, and Jagatkrti.